A study and survey on the service condition of barrier-free facilities in the transportation system with ergonomic evaluation - Seng Fat Wong; Lili Zhong; Weng Keong Chan; Weng Hou Leong; Kin Seng Ho (2012 IEEE International Conference on Industrial Engineering and Engineering Management, 2012)
This paper mainly conducts a study and survey on the service condition of barrier-free facilities in the transportation system. It is applied the ergonomic technology that including Forces Sensitive Application (FSA) pressure mapping system, electronic hand dynamometer, HumanCAD, and questionnaire survey to do the evaluation. The evaluation is focused on the elder and wheelchair user. The results can contribute to reduce the disorder problems for elder by the portable pedal design when the elder enters the vehicle. Moreover, the results of ergonomic analysis can scientifically find out the sitting posture problems for wheelchair users in ordinary vehicle and special designed vehicle.